Hubungan antara Syok Berkepanjangan (Prolonged Shock) dengan Kematian Anak Penderita Dengue Shock Syndrome di PICU/NICU RSUD Dr.Moewardi - Rizka Solehah; . Pudjiastuti; Leli Saptawati (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2013)
Dengue Shock Syndrome (DSS) is severe type of dengue infection which is the major cause of mortality. In Indonesia, DSS cases increase until 53%, the number of incidence are 500.000 cases every year, and its mortality is 1-5%. DSS is caused by plasma leakage which can leading to tissue hypoperfusion. If proper and timely management of DSS had delayed, DSS may result in multiple organ dysfunction syndrome (MODS) even death. The purpose of this research is to find out whether there is the relationship between prolonged shock and mortality of children with Dengue Shock Syndrome at PICU/NICU of RSUD Dr. Moewardi. This was an analytic observational study with cross sectional approach and purposive sampling technique. A sample of 61 study subject was selected by purposive sampling technique from children who aged 0-18 years, children who suffered Dengue Shock Syndrome and treated at PICU/NICU RSUD Dr. Moewardi in June 2006 - December 2011. The data obtained from PICU/NICU and medical records section of RSUD Dr. Moewardi. Statistical analysis was using chi square test and continued by using contingency coefficient test. Patients of prolonged shock DSS have higher mortality than patients of non-prolonged shock DSS, although the relation between them is low (p = 0.005; contingency coefficient = 0,335). The mortality risk were five times greater (OR= 5; CI 95%; 1,536 16,273). In this study, DSS was much found in girl (59,02%), children aged 6-12 years old (52,46%), and usually who had weak condition (67,21%), and good nutritional status because this study was done at area with good nutritional status was majority in children. There were significant relationship between prolonged shock and mortality of children with Dengue Shock Syndrome at PICU/NICU of RSUD Dr. Moewardi with low rate relation. Patients with prolonged shock DSS have higher risk of mortality than patients with non-prolonged shock DSS.